How the Supreme Court Made the Freedom of Speech More Free - Coscia, Monica (Colloquium: The Political Science Journal of Boston College, 2017)
This paper argues that the United States Constitution’s First Amendment guarantee of free speech is imperative to maintaining a free society, even if some members of that society find certain speech disagreeable or offensive. It contends that federal and state laws must obey the First Amendment’s guarantee of content neutrality, or acceptance of all viewpoints, in order to be considered constitutional. By delineating the progression of Supreme Court precedent regarding controversial speech through four landmark cases, this paper argues that the Court’s jurisprudence over the past half-century justly moved in a constitutional direction, because modern legal interpretation of the First Amendment has made free speech even freer than it was at the time of the First Amendment’s ratification. Finally, this discussion asserts that while the modern view of free speech may not align with the Founders’ opinions, it achieves their ultimate vision of an adaptable Constitution and a tolerant, open society.